Excited-state hydrogen atom abstraction initiates the photochemistry of β-2′-deoxycytidine1. Issue 3 (16th March 2015) - Szabla, Rafał; Campos, Jesús; Šponer, Judit E.; Šponer, Jiří; Góra, Robert W.; Sutherland, John D.
<x xml:space="preserve">Abstract</x> H–D exchange experiments and quantum-chemical calculations elucidate the mechanism of photoinduced anomerisation and nucleobase loss reactions observed in β-2′-deoxycytidine.